Dieta a base de palma forrageira para ovinos terminados em confinamento. - Santos, Luana Lira (2017)
Was evaluated the effect of replacing corn silage forage Palm associated with the tifton 85 hay or bagasse of sugar cane in Santa Inês sheep with initial body weight of 22.86 ± 2.87 kg on in vivo measurements, casting, morphometric correlation, attributes sensory meat performance and body weight components. 21 male lambs were confined in individual pens for 74 days receiving three diets-treatment: corn silage + concentrated (SM); Forage palm + hay of Tifton 85 + concentrated (FT); Forage Palm + sugarcane bagasse + concentrated (BC). The data was subjected to Tukey test to 5% probability. Average daily gain (0.25 vs 0.14 kg), cold carcass weight (13.31 vs 13.66 Kg), muscularity of loin (0.58 vs 0.40 kg) and liver weight (0.71 vs 0.49 kg) were higher (p < 0.05) for FT diet when compared to SM. The physico-chemical parameters of the flesh were not influenced (p > 0.05) by the treatments and presented an average of 20.06% for gross protein, 6.06% gross fat and 1.98 kgF/cm2. As for sensory analysis, there was no variation between the appearance, juiciness and softness attributes, with average notes of 7.30; 6.97 and 7.60. However, the meat from animals fed with SM had lower grades for odor (6.53) and flavor (6.53) compared to other treatments. The breast width and chest perimeter correlated highly with the body weight (0.68; 0.77) and the weight of the cold housing (0.82; 0.81). The forage palm associated with hay of tifton 85, in complete diets for sheep, confers greater weight gain, greater muscularity of the cold carcass and greater weight of organs when compared to animals fed with maize silage as a bulky unique in the formulation. Also confers superiority in flavor and odor, without compromising the sensory quality of meat and the quantitative characteristics of the beef carcass.